Energy of Smith graphs - Sharma, P.; Naresh, R.; Sharma, U. (Algebra and Discrete Mathematics, 2020)
In this manuscript, we have evaluated the energies of Smith graphs. In the course of the investigation, we found that only one Smith graph is hypo-energetic. Moreover, we have also established the energy bounds for Smith graphs.